Identification of carotenoid composition in selected 'ulam' or traditional vegetables in Malaysia - Mohd Zaifuddin, Fatimah Azzahra; Mohd Hassan, Norazian; Othman, Rashidi (2012)

(untitled)
Ulam or traditional vegetables in Malaysia comprise more than 120 species representing various families ranging from groundcovers, shrubs to trees. Ulam grow well and wild in the forest and forest fringes, in wastelands and wetlands, along streams and ditches, in paddy fields or in backyard gardens. The leaves, shoots, flowers, fruits, roots and rhizomes of the vegetables are eaten fresh as salad or cooked. They are consumed because of their taste, which adds variety and flavor to the diet,as well as for their health benefits. Ulam species are rich in carbohydrate, protein, mineral and vitamin. Unfortunately little information about the antioxidant activities and properties are available. In view of the lack of investigation of ulam antioxidant properties especially vitamin A activities, the aim of this research is to explore the composition and concentration of carotenoids in wide range of ulam species to enable future enhancement or enrichment through environment or genetic manipulation. This study established that ulam species differ greatly with respect to types and concentrations of carotenoids in leaves. A total of 10 species were evaluated for quantitative and qualitative carotenoid composition through spectrophotometry and HPLC analysis. The main carotenoids identified in these selected ulam were lutein,neoxanthin, violaxanthin, zeaxanthin and β-carotene. The ratio of these carotenoids varies between species.